2010
DOI: 10.1080/02640410903414160
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between body composition, body dimensions, and peak speed in cross-country sprint skiing

Abstract: In modern sprint cross-country skiing, strength and maximal speed are major determinants of performance. The aims of this study were to ascertain the anthropometric characteristics of world-class sprint skiers and to evaluate whether a specific body composition and/or body dimension characterizes a successful sprint skier. Our hypothesis was that body height and lean body mass are related to peak speed in double poling and diagonal stride. Fourteen male national and international elite skiers performed two pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 29 publications
4
54
1
1
Order By: Relevance
“…In roller skiing, the rear wheel is locked whereas on snow the ski needs to be compressed towards the snow to obtain grip while skiing. 24 From a practical point of view, the arm movement ("low shoulder") in the reposition phase is of great importance in order to lower the COM and compress the ski's chamber (with kick wax) to the snow to obtain high static friction and thus allow for effective propulsion by the legs. Whether this way of moving is restricted during on-snow-skiing in DIA with long poles needs to be further studied.…”
Section: It Appears That the Length Of The Ski Poles May Be An Impormentioning
confidence: 99%
“…In roller skiing, the rear wheel is locked whereas on snow the ski needs to be compressed towards the snow to obtain grip while skiing. 24 From a practical point of view, the arm movement ("low shoulder") in the reposition phase is of great importance in order to lower the COM and compress the ski's chamber (with kick wax) to the snow to obtain high static friction and thus allow for effective propulsion by the legs. Whether this way of moving is restricted during on-snow-skiing in DIA with long poles needs to be further studied.…”
Section: It Appears That the Length Of The Ski Poles May Be An Impormentioning
confidence: 99%
“…For cycling as an edurance sport, a variety of different anthropometric characteristics, training characteristics, and physiological variables have been identified as important predictors for race performance (Knechtle, 2014). Over the years, research has been conducted in an attempt to provide further insight into the extent that an athlete's body dimensions and composition influence performance (Stöggl et al, 2010). In cycling, it was demonstrated that individuals competing in sprint events possess a higher body mass and larger leg circumferences than distance cyclists (McLean & Parker, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A new addition to Nordic skiing is the sprint event. This event requires more strength and power (Stöggl et al, 2010) and may benefi t from a different nutritional approach.…”
Section: Nutrition Issuesmentioning
confidence: 99%
“…While earlier data showed a 35-40% prevalence of iron defi ciency and depletion (Meyer & Parker-Simmons, 2009), more recent data on blood profi les in skiers ( alpine and cross-country) show rising hemoglobin and hematocrit levels (Banfi et al, 2010;Morkeberg et al, 2009). Nevertheless, athletes should still be tested and adequate time to remedy low iron status should be provided, especially well ahead of altitude exposure (Stray-Gundersen et al, 1992).…”
Section: Common Nutrition Issues Among Winter Sport Athletesmentioning
confidence: 99%